Pobreza e fome, uma história contemporânea Temas, metodologias e estudos de caso - Queiroz, Ana Isabel; Direito, Bárbara; da Silva, Helena; Pinto, Lígia (Estratégica, 2022)
Poverty and hunger, a contemporary story analyzes poverty and hunger, current problems seen in a space-time dimension, bringing together multidisciplinary approaches from 29 researchers from the IHC and other research centers. Considering political, economic, social, cultural and environmental dimensions, it aims to stimulate critical thinking about environmental degradation, inequality and social discrimination, while also considering issues such as racism, the over-exploitation of humans and non-humans, gender issues, pollution and climate change. Published within the scope of the current programmatic project of the IHC and organized in three parts, this work identifies and reviews some of the most relevant themes for an understanding of the phenomena of poverty and hunger in contemporary Portugal.